Data classification and Information Security Management System (ISMS) awareness at Taskeater Bangladesh Limited - Afnan, Ajmain Fayek (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.